The Effect of Workload and Role Conflict on Employee Performance with Work Stress as a VariableModerate in Bank Representative OfficeIndonesia Pematangsiantar - Nurmaya Hutasoit; Elfitra Desi; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study focuses on assessing how Workload and Role Conflict affect Employee Performance, with Job Stress acting as a moderating factor at the Bank Indonesia Representative Office in Pematangsiantar. Quantitative methods were applied, using Structural Equation Modeling (SEM) analysis using SmartPLS 3.0. The sample consisted of employees from the office selected through purposive sampling. The results indicate that Workload and Role Conflict have a significant negative influence on Employee Performance, and Job Stress also negatively impacts performance. However, Job Stress does not act as a moderator between Workload, Role Conflict, and Employee Performance. These results highlight the need for management at the Bank Indonesia Representative Office in Pematangsiantar to effectively manage workload, role conflict, and employee stress levels to improve employee performance, productivity, and overall well-being.